Risk of Recurrence and Transition to Chronic Disease in Acute Central Serous Chorioretinopathy - Mohabati D; Boon CJF; Yzer S (Clinical Ophthalmology, 2020)
Danial Mohabati,1,2 Camiel JF Boon,1,3 Suzanne Yzer4 1Department of Ophthalmology, Leiden University Medical Center, Leiden, the Netherlands; 2Department of Ophthalmology, Rotterdam Ophthalmic Institute, Rotterdam, the Netherlands; 3Department of Ophthalmology, Academic Medical Center, University of Amsterdam, Amsterdam, the Netherlands; 4Department of Ophthalmology, Rotterdam Eye Hospital, Rotterdam, the NetherlandsCorrespondence: Suzanne YzerRotterdam Eye Hospital, Department of Ophthalmology, Schiedamse Vest 180, Rotterdam 3011 BH, the NetherlandsTel +31-10-4017777Fax +31-10-4017699Email S.Yzer@oogziekenhuis.nlPurpose: To study the risk of recurrence in acute central serous chorioretinopathy (aCSC) and to evaluate the risk of transitioning to chronic CSC.Patients and Methods: The medical records and multimodal imaging data of 295 aCSC cases were reviewed. Typical aCSC was defined as the presence of serous subretinal fluid (SRF), one focal leakage spot on fluorescein angiography (FA), retinal pigment epithelium (RPE) alterations limited in area to less than one optic disc diameter, and complete recovery from this first CSC episode. An increase in RPE alterations combined with persistent SRF was considered a sign of chronicity, which was determined in cases with > 12 months follow-up. The main outcome measures included final visual acuity, percentage of disease recurrence, and percentage of cases moving toward a chronic phenotype. Treatment strategies and their efficacy were also reviewed.Results: A total of 295 eyes in 291 patients with aCSC were included. Spontaneous recovery was awaited in 154 eyes (52%), whereas 141 eyes (48%) recovered following treatment. SRF recurrence occurred in 24% of untreated cases and in 4% of treated cases (p< 0.001). An analysis of 61 eyes that underwent an FA after ≥ 12 months of follow-up revealed increased RPE alterations in 22 eyes (36%), and 14 eyes (23%) had both an increase in RPE alterations and SRF recurrence.Conclusion: All aCSC cases recovered from the first disease episode, and none of the cases developed persistent SRF leakage. Among the cases for which long-term follow-up information was available, 36% showed a tendency toward chronicity in terms of increased RPE alterations, whereas 23% showed both an increase in RPE alterations and recurrent SRF. Early photodynamic therapy (PDT) may decrease the risk of recurrences.Keywords: acute central serous chorioretinopathy, chronic CSC, photodynamic treatment, recurrent CSC